An investigation on the use of coaching for performance (CFP) as a tool for bonus allocation in an organisation: a case of World Vision Zimbabwe - Musariyarwa, Bridget (Midlands State University, 2017)
This paper investigated on the use of Coaching for Performance as a tool for employee bonus allocations in an organisation. The argument was based on the over expenditures being experienced at World Vision Zimbabwe on bonus payments every year. The performance measurement tool in use at World Vision Zimbabwe was evaluated and its practicability on offices in the organisation that provide services that cannot be measured quantitatively was evaluated. The paper discussed the practicability of measuring individual performance so as to accurately allocate bonus payments. Different performance measurement techniques were discussed as according to literature. Furthermore, the different bonus allocation systems were also discussed as according to literature. The research brought to light the different problems associated with performance based bonuses. The research methodology that was used to carry out the investigation was discussed in the paper. The findings indicated that the half of the individual performance evaluations is based on managerial opinion which is subject to bias. The paper concluded that the organisation’s supervisors are not well versed with the supervisory skills required as they have no supervising workshops. The paper also concluded that linking performance to bonuses can be based on individual interests and hence leading to conflicts between employees in the organisation. Recommendations were given to the organisation according to the literature reviewed in the paper.